2017
DOI: 10.1152/ajpgi.00254.2016
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects and mechanisms of vagal nerve stimulation combined with electroacupuncture in a rodent model of TNBS-induced colitis

Abstract: The purpose of this study was to determine the effects and mechanisms of vagal nerve stimulation (VNS) and additive effects of electroacupuncture (EA) on colonic inflammation in a rodent model of IBD. Chronic inflammation in rats was induced by intrarectal TNBS (2,4,6-trinitrobenzenesulfonic acid). The rats were then treated with sham ES (electrical stimulation), VNS, or VNS + EA for 3 wk. Inflammatory responses were assessed by disease activity index (DAI), macroscopic scores and histological scores of coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 37 publications
8
97
0
Order By: Relevance
“…The autonomic nervous system was reported to be altered both structurally and functionally in IBD and more than 35% of patients with UC showed impaired parasympathetic function and overexcited sympathetic activity . The autonomic imbalance was reported to contribute to the inflammatory drive in IBD: sympathectomy improved experimental colitis and VNS improved colitis in animal models of inflammation . In the present study, we found that vagal efferent activity was decreased by administration of TNBS and DSS and significantly increased by SNS and VNS.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The autonomic nervous system was reported to be altered both structurally and functionally in IBD and more than 35% of patients with UC showed impaired parasympathetic function and overexcited sympathetic activity . The autonomic imbalance was reported to contribute to the inflammatory drive in IBD: sympathectomy improved experimental colitis and VNS improved colitis in animal models of inflammation . In the present study, we found that vagal efferent activity was decreased by administration of TNBS and DSS and significantly increased by SNS and VNS.…”
Section: Discussionsupporting
confidence: 57%
“…Sixty‐four male SD rats were randomized into eight groups (8 rats in each): 7 treated with TNBS and one group with saline (Control group). The rats were deprived of food for at least 24 hours; then a 7.5‐cm long soft tube was inserted into the colon and 2, 4, 6‐Trinitrobenzenesulfonic acid (TNBS, Sigma‐Aldrich) was injected at a dose of 22.5 mg per rat in 40% ethanol (total volume, 0.75 mL) . To ensure the retention of TNBS within the colon, the rats were maintained in a slightly head‐down position for 10 minutes following the administration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed a significant improvement of colitis under VNS, a decrease of pro-inflammatory cytokines (TNFα and IL-6), and an improvement of HRV. More recently, Jin et al (Jin et al, 2016) showed that chronic VNS improves inflammation in TNBS-treated rats by inhibiting pro-inflammatory cytokines via an autonomic mechanism; addition of noninvasive electro-acupuncture to VNS enhanced the anti-inflammatory effect of VNS.…”
Section: Experimental Rationalementioning
confidence: 99%